PENCATATAN AKUNTANSI SEKTOR PUBLIK - Negina Kencono Putri; Siti Maghfiroh (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
Public sector accounting is an information system that identifies, organizes, and communicates information on the economy and public sector entities. Public economic information is useful for decision-making on: (1) Allocation of economic resources, (2) Public services, (3) Performance of public sector organizations, (4) Assessment of liquidity capabilities, (5) Distribution of income and economic stability. Therefore, it is important for government institutions to understand how public sector accounting to achieve accountability of financial statements. This service was carried out in Karangreja Village, Cipari District, Cilacap Regency, which was attended by all karangreja village officials, along with PKK mothers from Karangreja Village. The purpose of implementing this service is to (1) provide an understanding of how public sector accounting in Indonesia, (2) Provide accounting skills to all PKK staff and mothers. After being given an understanding and skills in accounting in the public sector, it is hoped that it can be applied and can increase the accountability of the financial statements of Karangreja village.